Effects of Enteromyxum spp. (Myxozoa) infection in the regulation of intestinal E‐cadherin: Turbot against gilthead sea bream - Ronza, Paolo; Estensoro, Itziar; Bermúdez, Roberto; Losada, Ana Paula; Pérez-Cordón, G.; Pardo, Belén G.; Sitjà-Bobadilla, Ariadna; Quiroga, María Isabel (Journal of Fish Diseases, 2020)
Enteromyxoses are relevant diseases for turbot and gilthead sea bream aquaculture. The myxozoan parasites invade the intestinal mucosa, causing a cachectic syndrome associated with intestinal barrier alteration; nonetheless, their pathological impact is different. Turbot infected by Enteromyxum scophthalmi develop more severe intestinal lesions, reaching mortality rates of 100%, whereas in E. leei‐infected gilthead sea bream, the disease progresses slowly, and mortality rates are lower. The mechanisms underlying the different pathogenesis are still unclear. We studied the distribution and expression changes of E‐cadherin, a highly conserved protein of the adherens junctions, in the intestine of both species by immunohistochemistry and quantitative PCR, using the same immunohistochemical protocol and common primers. The regular immunostaining pattern observed in control fish turned into markedly irregular in parasitized turbot, showing an intense immunoreaction at the host–parasite interface. Nevertheless, E‐cadherin gene expression was not significantly modulated in this species. On the contrary, no evident changes in the protein distribution were noticed in gilthead sea bream, whereas a significant gene downregulation occurred in advanced infection. The results contribute to the understanding of the different host–parasite interactions in enteromyxoses. Host and parasite cells appear to establish diverse relationships in these species, which could underlie the different pathological picture. This work has been funded by the Spanish Ministry of Economy and Competitiveness and the European Regional Development Fund (ERDF) through the projects AGL2015‐67039‐C3‐1‐R, AGL2015‐67039‐C3‐3‐R and AGL‐2013‐48560‐R and by the Horizon 2020 Framework Programme through ParaFishControl Project (634429). I.E. was contracted under APOSTD/2016/037 grant by the “Generalitat Valenciana” and G.P.‐C. under the “Juan de la Cierva” programme, granted by the Spanish Ministry of Science and Innovation (JCI‐2011‐09438). Peer reviewed